BLENDED LEARNING (MIXED EDUCATION) AND ITS ADVANTAGES IN ENGLISH CLASSES - Khodjiyeva Iroda, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This in the article English language blended learning in teaching education ) method relevance , content and advantages analysis Mixed education traditional audience training with online education tools harmonization through effective to the results achieve opportunity gives . In the study Uzbekistan education in the system this from the method use situation , its advantages and to the surface coming problems seeing The results of the blended learning method students independent education development , English in the language communicative competence increase and lesson efficiency in strengthening important place to hold showed .